2011
DOI: 10.1158/1535-7163.mct-10-0474
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidylcholine Pretreatment Reduces VLA-4 and P-Selectin–Mediated B16.F10 Melanoma Cell Adhesion In vitro and Inhibits Metastasis-Like Lung Invasion In vivo

Abstract: Lysophosphatidylcholine (LysoPC) is an important intermediate in degradation and biosynthesis of phosphatidylcholine (PC). Reduced plasma LysoPC levels observed in patients with advanced cancer indicate a deregulation of LysoPC metabolism in metastasis. Recent data showed strong antimetastatic effects of liposomes consisting of saturated PC in a murine pancreatic metastasis model. LysoPC, generated from saturated PC after accumulation of the liposomes in tumor tissue, might be contributing to these effects. Ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 50 publications
5
48
1
Order By: Relevance
“…In a melanoma model, both blockade and inhibition of VCAM-1 have been shown to significantly reduce liver metastasis (16,27). Similarly, disruption of the interaction between very late antigen-4, the natural ligand to VCAM-1, on tumor cells and endothelial VCAM-1 reduces both adhesion of metastatic renal cell cancer cells to endothelial cells in vitro (28) and incidence of lung metastases in vivo (29). Moreover, several human tumor cell lines that metastasize to the lung show greater expression of very late antigen-4 than nonmetastatic lines (30).…”
Section: Discussionmentioning
confidence: 99%
“…In a melanoma model, both blockade and inhibition of VCAM-1 have been shown to significantly reduce liver metastasis (16,27). Similarly, disruption of the interaction between very late antigen-4, the natural ligand to VCAM-1, on tumor cells and endothelial VCAM-1 reduces both adhesion of metastatic renal cell cancer cells to endothelial cells in vitro (28) and incidence of lung metastases in vivo (29). Moreover, several human tumor cell lines that metastasize to the lung show greater expression of very late antigen-4 than nonmetastatic lines (30).…”
Section: Discussionmentioning
confidence: 99%
“…Although LPCs are typically regarded as pro-inflammatory mediators, they were increased in inflammatory diseases (27,28). A previous series of studies have demonstrated a protective effect of LPCs against diseases, including type 2 diabetes (29), cancer (30) and inflammatory diseases (31).…”
Section: Trend ------------------------------------------------------mentioning
confidence: 99%
“…In the vascular endothelium, LPC increased permeability and expression of proinflammatory mediators such as adhesion molecules and cytokines. However, saturated LysoPC in high concentrations reduced melanoma cell adhesion in vitro (Jantscheff et al, 2011). Certain lysophospholipids such as ether-linked lysophosphatidylcholine are acetylated by a specific acetyltransferase to form platelet activating factors (Hanahan, 1986).…”
Section: Classes Of the Main Phospholipids And Their Abundancementioning
confidence: 99%